Factors influencing SME owners' continuance intention in Bangladesh: a logistic regression model - Aghaei, Iman; Sokhanvar, Amin (Springer Heidelberg, 2020)
The purpose of this paper is to identify the critical determinants of Bangladeshi small and medium-sized enterprises' intention to continue their business. 1724 business owners participated as respondents in this survey. Using logistic regression, our results suggest that continuance intention is affected positively by innovation, informality, risk attitude, and debt. On the other hand, the age of the business owner and the size of firm do not play any significant role in this intention. The probability of continuance in the presence of each of these factors is also calculated in Manufacturing, Service, and Trade sectors separately. Understanding the influential determinants of continuance intention of business owners would help the policy makers to devise appropriate policies from a better insight to support the industry in different sectors.
Keywords: Business owner; Continuance intention; Informality; Innovation; Risk attitude